Calcium hydroxide intracanal dressing removal with different rotary instruments and irrigating solutions: A scanning electron microscopy study - Kuga, Milton Carlos [UNESP]; Tanomaru-Filho, Mário [UNESP]; Faria, Gisele [UNESP]; Só, Marcus Vinicius Reis; Galletti, Tiago; Bavello, José Roberto Sampaio (FapUNIFESP (SciELO), 2010)
This study evaluated the efficacy of 2 types of rotary instruments employed in association with sodium hypochlorite (NaOCl) or EDTA in removing calcium hydroxide (CH) residues from root canals dentin walls. Forty-two mandibular human incisors were instrumented with the ProTaper System up to F2 instrument, irrigated with 2.5% NaOCl followed by 17% EDTA and filled with a CH intracanal dressing. After 7 days, the CH dressing was removed using 4 techniques: NiTi rotary instrument size 25, 0.06 taper (K3 Endo) and irrigation with 17% EDTA (Group 1), NiTi rotary F1 instrument (ProTaper) and irrigation with 17% EDTA (Group 2), NiTi rotary instrument size 25, 0.06 taper and irrigation with 2.5% NaOCl (Group 3) and NiTi rotary F1 instrument and irrigation with 2.5% NaOCl (Group 4). Two roots without intracanal dressing were used as negative controls. Teeth were evaluated by scanning electron microscopy, in the cervical and apical canal thirds. None of the techniques removed the CH dressing completely. In the apical and cervical thirds, F1 instrument was better than instrument size 25, 0.06 taper in removing CH residues (p<0.05), regardless of the final irrigating solution. No difference was found between the irrigating solutions in the groups of F1 instrument and of instrument size 25, 0.06 taper (p>0.05). The negative controls had no CH residues on the dentin walls. In conclusion, the ProTaper F1 instrument was better than K3 Endo instrument size 25, 0.06 taper in the removal of CH intracanal medication, regardless of irrigating solution used.
Keywords: Calcium hydroxide; EDTA; Intracanal dressing; Rotary instruments; Sodium hypochlorite; biomedical and dental materials; calcium hydroxide; edetic acid; hypochlorite sodium; root canal filling material; chemistry; comparative study; dental equipment; endodontics; equipment design; human; incisor; instrumentation; lavage; mandible; methodology; nonparametric test; tooth pulp; ultrastructure; Calcium Hydroxide; Dental Instruments; Dental Pulp Cavity; Edetic Acid; Equipment Design; Humans; Incisor; Mandible; Root Canal Filling Materials; Root Canal Irrigants; Root Canal Preparation; Sodium Hypochlorite; Statistics, Nonparametric; Therapeutic Irrigation